PENGARUH PELAKSANAAN TATA KELOLA DAN TATA PAMONG TERHADAP KINERJA DI STEBIS IGM PALEMBANG - Dian Tri Utami; Mislahatul Amma; Muhtar Pido; Amir Salim (Jurnal Ilmiah Mahasiswa Ekonomi Syariah (JIMESHA), 2021)
Governance is a system that guarantees the implementation of the principles of credibility, accountability, responsibility and justice. IGM STEBIS Pamong Governance was developed by establishing and enforcing a system of values and norms, as well as internal motivation. The development of the civil service system is expected to be able to empower a management system that is oriented towards the principles of healthy tertiary management. This organizational management arrangement aims to form an administrative system that functions to increase effectiveness, efficiency and productivity in the effort to realize the vision, mission implementation, discipline and institutional integrity.